(untitled) (Asian Journal of Medical and Biological Research, 2017)
The study was conducted aiming at the isolation and identification of pathogens from poultry feed manufactured by four different brands namely A (broiler starter), B (broiler finisher), C (layer starter) and D (layer finisher) sold in retail stores of Rangpur city of Bangladesh. All these samples were collected from four randomly chosen outlets and analyzed by culturing in different culture media such as Nutrient broth (NB), Nutrient agar (NA), Salmonella-Shigella (SS) agar, Eosin methylene blue (EMB) agar, MacConkey agar, Triple sugar iron (TSI) agar slant, Motility, Indole, Urease (MIU) and Saboraud Dextrose agar (SDA) media. The bacterial agents were isolated and examined under light microscope for their gross morphological and conventional biochemical characteristics. The bacteriological analyses were done at the Microbiology Laboratory of Hajee Mohammad Danesh Science and Technology University, Dinajpur during the period of January to June, 2014. Total bacterial colonies of all the samples were counted separately according to the American Public Health Association, using nutrient agar medium for total viable count (TVC), Eosine methylene blue (EMB) agar media for total E. coli count (TEC) and Salmonella-Shigella agar for TSC (total salmonella count). Saboraud Dextrose agar (SDA) media was used for detection of fungus. The virulence effect of the organism present in feed were observed by inoculating the organism in poultry. Recorded result showed that average TVC of feed sample A, B, C and D were 5.45x106, 3.28x105, 5.14x106 and 4.53x105 CFU/gm (colony forming unit per gram) respectively. TEC of feed sample A, B, C and D were recorded 6.25x105, 8.26x103, 5.52x105 and 5.65x104 CFU/gm respectively. TSC of feed sample A, B, C and D were recorded 3.15x104, 2.68x103, 4.46x103 and 1.19x104 CFU/gm respectively. The highest TVC, TEC and TSC were found in broiler starter (feed sample A) and lowest TVC, TEC and TSC were found in broiler finisher (feed sample B). Fungal count was 1.85x105 CFU/ gm in layer finisher (feed sample D) could be as a result of their high pathogenecity as reported by researchers elsewhere. These organisms can cause several poultry and farm animal infections specially mycotoxicosis having public health significance to both human and poultry. The presence of high numbers of E. coli and Salmonella spp. in poultry feed were indicative of poor hygienic practices during manufacture, post process contamination and unsatisfactory transportation and reservation. Therefore reinforce the need for preventive control measures, hygienic handling and processing of feeds to reduce the risk of potential human health hazards. Asian J. Med. Biol. Res. March 2017, 3(1): 52-60